Financial programming and policy : the case of Turkey - Barth, Richard C.; Aganina, Irina; Hemphill, William Loehr; IMF Institute (Washington, D.C. : IMF Institute, International Monetary Fund, 2000)
This volume contains a series of workshops designed to introduce readers to the process of formulating a macroeconomic adjustment program. The design of a consistent set of policies intended to move an economy toward internal and external balance is a central task of the financial programmimg courses offered by the IMF Institute. The workshops present the macroeconomic concepts and accounting and behavioural relationships needed to develop, step-by-step, a reference scenerio for the Turkish economy for a selected program year.
Includes bibliographical references.
oif 17/07/14
Loan
Keywords: Finance; Structural adjustment (Economic policy); Industrial productivity; Prices; Turkey; Turkey